Preliminary survey of feline intestinal parasites in Ghana - Amissah-Reynolds, Papa Kofi; Ofori, Samuel Ayetibo (The Asia Journal of Applied Microbiology, 2023)
Cats can host an array of parasite species. This is particularly evident in sub-Saharan Africa, where climatic conditions favour parasites and their vectors, and pets are given little medical attention. The presence of parasites in cats results in significant morbidity in these companion animals. Proximity of infected cats to humans also favours zoonotic transmissions. This study aimed at ascertaining the prevalence and diversity of parasites in cats. A total of 90 feline faecal samples were examined using floatation techniques. Overall, 75 cats (83.3%) were infected with at least one of six parasite species. Toxocara ova were found in 35 (38.9%), hookworm ova in 20 (22.2%), Isospora in 19 (21.1%), Capillaria in 17 (18.9%), pinworm eggs in 5 (5.6%) and flukes in 4 (4.4%) cats respectively. Sex of cats was a significant determinant of infections. This study demonstrates environmental contamination with feline parasites of zoonotic importance, thus necessitating a One-Health surveillance to minimize zoonotic risks from these companion animals. Cats play active roles in the transmission of multiple parasites of zoonotic importance in Ghana.